Evaluación de tres niveles de microorganismos eficientes activados (EM-A) en la fertilización de cultivos de forraje verde hidropónico (FVH) en la quinta experimental Punzara de la UNL - Villalta Castillo, Marisol (2014)
Activated efficient microorganisms (EM-A) were produced and samples were sent to the microbiology laboratory to identify the constituents trains. Subsequently their effect on hydroponic green forage (HGF) fertilization was evaluated. The forage oats were grown inside a greenhouse to which certain adjustments were made. Seeds were planted in plastic trays and fine sawdust was used as a substrate, the planting density was 200g of oats per tray. The seeds were selected and hydrated by filling a bucket with water and soaking them for a period of 4 hours; from the process of pre germination the seed was placed in the trays with the substrate. We considered 21 days of growth from germination. To study the proposed variables, we used a complete lyrandomized experimental design with 4treatments and7 repetitions; utilizing28experimental units (trays), 7 for each treatment. During the experiment alstage, the following variables were studied: The plant development(height incm)at 7,14and 21 days of growth and biomass production at day21 of growth. The greatest plant growth was recorded in Treatment 2, with 0.25% of efficient activated microorganisms and an average height of23.8cm. This same treatment also yielded the best performance with an average biomass of 1,951 kg per tray. The percentage of protein and fibre were studied, for which samples of forage from each of the treatments were sent to the laboratory. The result showed that the percentage of protein at 21 days was higher in both the dry base (BS) and the fed (TCO) in the controlled treatment (i.e. without fertilization with efficient activated microorganisms) with 1.38% in TCO and 9.60% in BS. In terms of fibre it was greater in treatment 2, both in TCO and BS with 5.95% and 41% respectively. In the statistical analysis, an ANOVA test was performed using the data obtained; there sult indicated that there is a highly significant difference between the treatments therefore the Duncan test of profitability was applied, the price per kg of HGF oatproducedwas0.23 USD in the controlled treatment (without efficient activated microorganisms), this being the pricier due to the higher percentage of protein compared to the other forage treatments, however this price does not justify the investment, so it is not considered profitable to market hydroponic green forage oats in our medium, although one should allocate the forage for domestic animal consumption.